Exploring the complex policy formulation process of the draft Control of Marketing of Alcoholic Beverages Bill in South Africa - Bertscher, Adam (Department of Public Health and Family Medicine, 2017)
International literature suggests that corporate influence is evident when governments attempt to regulate products implicated in non-communicable disease, such as tobacco, asbestos, pollution, and foods, such as trans-fat, salt and sugar. These lifestyle diseases are aptly referred to as 'industrial epidemic', since industries profit from the public's continued consumption of such products. Of these 'industrial epidemics', alcohol is a major contributor to the health burden in South Africa. In the year 2000, 7.1% of all deaths and 7% of total disability-adjusted life years have been ascribed to alcohol-related harm in the country. The tangible and intangible costs of alcohol-related harm amount to 10-12% of South Africa's 2009 Gross Domestic Product. Literature suggests that limiting alcohol use could prevent the incidence of violence, injury, risky sexual behaviours, several forms of cancer, and neuropsychiatric and physical diseases. The World Health Organisation (WHO) released two documents, The Global strategy to reduce the harmful use of alcohol (2010b) and The Global Status Report on Non-communicable Diseases (2010a), detailing the negative effects of alcohol consumption for societies. Both documents recommend that decreasing alcohol consumption through banning of alcohol advertising would have significant public health benefits, although an integrated strategy is necessary to mitigate alcohol abuse including taxation, increasing prices, limiting places of sales and increasing education on the topic. In response, the South African government proposed a draft regulation aimed at restricting alcohol advertising as an evidence-based upstream intervention. The draft Control of Marketing of Alcoholic Beverages Bill is in the process of undergoing impact assessments to determine the impact this regulation may have on South African society. Literature suggests that industry employs various political strategies to avoid such regulation. However, little is known about the strategies the alcohol industry potentially uses to influence policy development in South Africa. There is a lack of knowledge on the current strategies used by the alcohol industry to influence policy; the draft Control of Marketing of Alcoholic Beverage Bill is a case in point. This study sought to explore the complex policy formulation process in South Africa, using the draft Control of Marketing of Alcoholic Beverages Bill as a tracer case and focused on the alcohol industry, as a central actor, to understand how it - together with other actors - may influence this process. A qualitative case study approach was used, which included stakeholder mapping, 10 in-depth interviews and review of approximately 240 documents. This study makes use of two conceptual frameworks. The first framework, Berlan et al. (2014) is used to understand policy formulation as a process with multiple facets. The second framework, Roberts et al. (2004), provides four typologies of political strategies that health reformers/advocates/lobbyists employ to influence the policy process. A thematic analysis was used to analyse the data. Key themes identified were: (1) Competing and shared values - different stakeholders promote conflicting ideals for policymaking; (2) Inter-department jostling - different government departments seek to protect their own interests, hindering policy development; (3) Stakeholder consultation in democratic policymaking – policy formulation requires consultation even with those opposed to regulation; (4) Battle for evidence – industry sought to assemble evidence to use as 'ammunition' in opposition to the ban. It was concluded that networks of actors with financial interest use diverse strategies to influence policy formulation processes to contest proposed regulation. Using the policy formulation process of the draft Control of Marketing of Alcoholic Beverages Bill as a tracer case, this research is a critical enquiry into how the for-profit industry affects public health interests in South Africa; such a critical enquiry could also be applied to other non-communicable diseases. Research suggests that industries have more difficulty in pushing their agenda when policymakers are well informed, are aware of the evidence-based practice and are not motivated by economic arguments alone. There is also a lack of research that focuses on health policy analysis in low and middle-income countries, and there is a lack of research focusing on the policy formulation process in particular. Therefore, this research aims to fill a gap in addressing a lack of research on health policy analysis in the context of a middleincome country. The implications of the study are that measures to insulate policy development are needed to prevent industry influence potentially undermining public health goals, such as: government to moderate certain consultations with industry; industry to declare conflict of interest; guidelines for bureaucrats and policymakers to advise on whose evidence to consider; and guidelines for bureaucrats and policymakers to assess quality of evidence.